2009
DOI: 10.1123/jsep.31.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical and Ergogenic Effects of Synchronous Music during Treadmill Walking

Abstract: The present study examined the impact of motivational music and oudeterous (neutral in terms of motivational qualities) music on endurance and a range of psychophysical indices during a treadmill walking task. Experimental participants (N = 30; mean age = 20.5 years, SD = 1.0 years) selected a program of either pop or rock tracks from artists identified in an earlier survey. They walked to exhaustion, starting at 75% maximal heart rate reserve, under conditions of motivational synchronous music, oudeterous syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(171 citation statements)
references
References 45 publications
12
151
1
7
Order By: Relevance
“…Studies have demonstrated that, although music moderates RPE at low-to-moderate intensities of exercise, it does not moderate RPE at intensities beyond anaerobic threshold (e.g., Bharani, Sahu, & Mathew, 2004;Boutcher & Trenske, 1990). Nonetheless, recent findings have served to challenge extant theory (e.g., Rejeski, 1985;Tenenbaum, 2001) insofar as appropriately selected music appears to moderate in-task affect during high-intensity activities (Hutchinson et al, 2011;Karageorghis et al, 2009). These findings were re-examined in the present study using a different exercise modality (swimming).…”
Section: Mechanisms Underlying the Effects Of Music During High-intenmentioning
confidence: 76%
See 3 more Smart Citations
“…Studies have demonstrated that, although music moderates RPE at low-to-moderate intensities of exercise, it does not moderate RPE at intensities beyond anaerobic threshold (e.g., Bharani, Sahu, & Mathew, 2004;Boutcher & Trenske, 1990). Nonetheless, recent findings have served to challenge extant theory (e.g., Rejeski, 1985;Tenenbaum, 2001) insofar as appropriately selected music appears to moderate in-task affect during high-intensity activities (Hutchinson et al, 2011;Karageorghis et al, 2009). These findings were re-examined in the present study using a different exercise modality (swimming).…”
Section: Mechanisms Underlying the Effects Of Music During High-intenmentioning
confidence: 76%
“…There are now a number of well-controlled studies in the literature that attest to the psychological, psychophysical, and ergogenic effects of music across a wide range of physical activity modalities (e.g., Hutchinson et al, 2011;Karageorghis et al, 2009;Rendi et al, 2008). Many of the effects can be linked to existing theoretical frameworks to account for effects such as dissociation (Rejeski, 1985;Tenenbaum, 2001) or increased work output/efficiency through entrainment (Large, 2000).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have tested effects of synchronous music, with ergogenic effects reported in treadmill walking 9 , cycle ergometry 10 , and 400 m running 11 . Synchronous use of music represents a form of auditory-motor synchronisation in which a runner and the music serve as oscillators; each generating its own rhythm yet sharing a common frequency 12 .…”
Section: Introductionmentioning
confidence: 99%